Entrepreneurial school culture model development: centralized implementation in Malaysian schools - Ghazali, Siti Sabihah; Abdul Kadir, Suhaida; Asimiran, Soaib; Krauss, Steven Eric (Human Resource Management Academic Research Society, 2019)
This paper discusses the development of entrepreneurial school culture in schools based on the models available in the current business discipline and its suitability in the education system. The emergence of entrepreneurial culture within a school as a non-profit organization is new and require vast improvement and enhancement method. In the Malaysian education system, the centralized education system practiced among schools under the government authorities do challenge all the school leaders to explore and develop entrepreneurial culture among students. For that purpose, this paper integrated models of entrepreneurial culture based on prior studies. Thus, this paper recommends models to be applied by the school principals in developing entrepreneurial school culture.